The Soil Diagnostic Method to Formulate Fertilizer Requirements for Coffee Trees in Côte d'Ivoire - , Eboa Christophe Ghislain Eponon, Koffi Fernand Jean-Martial Kassi, Konan Didier Kouamé, Didier Snoeck, Tieba Victor Ouattara, Maméri Camara, Mamadou Cherif, Daouda Kone (Archives of Current Research International, 2023)
Coffee is a crop that exports significant amounts of minerals from the soil, particularly through crop and pruning products. Maintaining sustainable productivity requires good knowledge and rational management of factors related to soil fertility and plant nutritional status, which would limit production. The objective of this study was to diagnose the mineral requirements of coffee plants in different production regions in order to recommend nutrient quantities adapted to the characteristics of each soil type for sustainable coffee production. Chemical analysis of 156 soil samples representative of the soil units of the coffee growing areas using a soil diagnostic model specific to coffee fertilization was used to determine the nutrient requirements of each soil unit studied. The results generally indicate that soil fertility levels were below the reference threshold values. Nutrient inputs are essential for all soils under coffee in large production areas. Nitrogen inputs are required in all soil units studied. The majority of the soils also showed a very pronounced potassium and calcium deficiency, while the phosphorus deficiency was not very pronounced. Magnesium, although generally in sufficient quantity in soils, has been readjusted to respect the balance in exchangeable bases. The amounts of nutrients to be supplied varied from one soil unit to another. Soils with low organic matter content showed relatively high requirements. Recommendations for appropriate soil fertility management per soil unit were presented in this work.